(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the baseline knowledge and practices related to the 5S management method among healthcare workers at selected commune health stations in Thanh Hoa province, and to evaluate the effectiveness of 5S training and implementation on improving healthcare workers’ knowledge and practices. Methods: The intervention study was carried out at commune health stations representing four regions of the province (mountainous area – Cam Thuy District, lowland – Trieu Son District, urban – Thanh Hoa City, coastal – Nghi Son Town). The intervention activities included theoretical training, guidance on 5S practice, and supportive supervision. Results: Before the intervention, the average score for general 5S knowledge was 6.55 points, with 48.7% achieving the required level. After the intervention, the average score increased to 7.62 points, with the achievement rate rising to 78.24%. The score for knowledge of applying 5S at work increased by 1 point (from 3.41 to 4.41). The average scores for all 5S knowledge categories increased significantly: “Sort” increased by 0.83 points; “Set in order” by 1.08 points; “Shine” by 0.75 points; “Standardize” by 1.06 points; and “Sustain” by 1.43 points. The knowledge score for applying 5S in management and leadership at health stations increased by 1.07 points after the intervention (from 3.51 to 4.58). Implementation of 5S at the health stations showed clear improvements in the working environment, leadership awareness, and the maintenance of practices. Conclusion: Training combined with direct on-site guidance significantly improved 5S knowledge and practices among HCWs at commune health stations. The results demonstrate that 5S is a feasible and impactful model for strengthening quality management across the primary healthcare system in Thanh Hoa province.